2003
DOI: 10.2337/diabetes.52.7.1770
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome Proliferator–Activated Receptor-α Agonist Treatment in a Transgenic Model of Type 2 Diabetes Reverses the Lipotoxic State and Improves Glucose Homeostasis

Abstract: Abnormalities in insulin action are the characteristics of type 2 diabetes. Dominant-negative muscle-specific IGF-I receptor (MKR) mice exhibit elevated lipid levels at an early age and eventually develop type 2 diabetes. To evaluate the role of elevated lipids in the progression of the diabetic state, MKR mice were treated with WY14,643, a peroxisome proliferator-activated receptor (PPAR)-alpha agonist. WY14,643 treatment markedly reduced serum fatty acid and triglyceride levels within a few days, as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
115
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(130 citation statements)
references
References 57 publications
11
115
0
Order By: Relevance
“…FENO and gemfibrozil) for the treatment of hypertriacylglycerolaemia in type 2 diabetic patients, their effect on insulin sensitivity in humans has not been rigorously examined and conflicting results have been reported [9][10][11][12][13][14]. Studies in rodents conclusively demonstrate that PPAR-α activation with FENO and other more potent PPAR-α agents enhances peripheral (muscle) and hepatic insulin sensitivity [4][5][6][7][8]. Although PPAR-α-null mice do not manifest any obvious alteration in insulin sensitivity [42], PPAR-α activation in nutritional (high-fat diet), genetic (Zucker obese fa/fa rat), and lipoatrophic (A-ZIP/ F-1) models of insulin resistance markedly improves insulin sensitivity [4,7,43] and reduces visceral fat in the two former models.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…FENO and gemfibrozil) for the treatment of hypertriacylglycerolaemia in type 2 diabetic patients, their effect on insulin sensitivity in humans has not been rigorously examined and conflicting results have been reported [9][10][11][12][13][14]. Studies in rodents conclusively demonstrate that PPAR-α activation with FENO and other more potent PPAR-α agents enhances peripheral (muscle) and hepatic insulin sensitivity [4][5][6][7][8]. Although PPAR-α-null mice do not manifest any obvious alteration in insulin sensitivity [42], PPAR-α activation in nutritional (high-fat diet), genetic (Zucker obese fa/fa rat), and lipoatrophic (A-ZIP/ F-1) models of insulin resistance markedly improves insulin sensitivity [4,7,43] and reduces visceral fat in the two former models.…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular fatty acids and their derivatives interfere with insulin-stimulated glucose metabolism, through an effect on the insulin-signalling pathway, possibly by activating protein kinase C [1,44]. In rodents it has been suggested that PPAR-α activation increases fatty acid oxidation, thus decreasing intramyocellular lipid content and improving insulin sensitivity [4][5][6][7]. In contrast, PPAR-α-null mice are protected from high-fat diet-induced insulin resistance [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one study from our laboratory (69) and in several others by Muoio and co-workers (2,66,70), the rates of fatty acid oxidation have been shown to be greater in mitochondria obtained from red muscle than in mitochondria obtained from white muscle. These studies suggest that there are intrinsic differences in the capacities to oxidize fatty acids by red and white muscle mitochondria.…”
Section: Pgc-1␣-induced Fatty Acid Oxidation-mentioning
confidence: 99%
“…A reduction in circulating or intracellular lipids by activation of PPAR-␣ improved insulin sensitivity and the diabetic condition of mice. 34 In adipocytes, skeletal muscle, and pancreatic ␤-cells, lipids are mobilized by the hormone-sensitive lipase, which deficiency results in a moderate impairment of insulin sensitivity. 35 …”
Section: Correction Of Hypertriglyceridemiamentioning
confidence: 99%